The determinants firm performance among Women Entrepreneur Small and Medium Enterprises (SME) in the Northern Region - Azmi, Nul Khayril Haziqah; Abdull Rahman, Nurul Labanihuda; Arifin, Muhammad Aiman; Shafai , Nor Anis (International Journal of Accounting, Finance and Business, 2025)
Malaysia has the biggest e-commerce industry in ASEAN, which has helped small and medium-sized businesses expand significantly. Nevertheless, numerous SMEs have trouble with long-term viability and encounter obstacles. Therefore, the purpose of this study is to close the knowledge gap by determining firm performance among women entrepreneurs in small and medium enterprises in the Northern Region, Malaysia. A quantitative method was adopted in this study, and partial least squares will be used to evaluate the research data. Finally, the results of the study will contribute to SMEs and women entrepreneurs to improve their firm performance in the future